Do Deductive and Probabilistic Reasoning Abilities Decline in Older Adults?. Issue 4 (December 2016) - Tommerdahl, Jodi M.; McKee, Will; Nesbitt, Monica; Ricard, Mark D.; Biggan, John R.; Ray, Christopher T.; Gatchel, Robert J.
Abstract : This present study investigated whether older adults' ability to accurately discriminate between deductive and probabilistic reasoning tasks declines with age, and whether this ability correlates with cognitive ability as measured by the Montreal Cognitive Assessment (MoCA) test. Seventy‐eight adults (65–92 years) were tested for their abilities to carry out deductive and probabilistic reasoning. Pearson correlations were conducted to determine the relationships among age, MoCA, deductive reasoning, probabilistic reasoning, and overall discrimination ability. Separate single‐factor analyses of variance were used to determine differences across age groups (65–74, 75–84, 85–94) on the MoCA, deductive and probabilistic reasoning, and overall discrimination ability. Ability to discriminate between the two tasks did not decline with age, nor did they correlate with scores of cognitive ability as measured by the MoCA. Furthermore, those with MoCA scores showing mild cognitive impairment appeared to retain all of these abilities. This leads to the conclusion that reasoning abilities may be retained while general cognitive skills decline. This in turn supports the notion that reasoning, both deductive and probabilistic, may be more domain specific than they are often considered to be.